2008
DOI: 10.1016/j.neuro.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic suppression of oxidative damage and dendritic degeneration following kainic acid-induced excitotoxicity in mouse cerebrum

Abstract: Intense seizure activity associated with status epilepticus and excitatory amino acid (EAA) imbalance initiates oxidative damage and neuronal injury in CA1 of the ventral hippocampus. We tested the hypothesis that dendritic degeneration of pyramidal neurons in the CA1 hippocampal area resulting from seizure-induced neurotoxicity is modulated by cerebral oxidative damage. Kainic acid (KA, 1 nmol/5 μl) was injected intracerebroventricularly to C57Bl/6 mice. F 2 -isoprostanes (F 2 -IsoPs) and F 4 -neuroprostanes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 73 publications
0
36
0
1
Order By: Relevance
“…KA-induced SE following systemic or intracerebroventricular injection of the drug initiates neuronal injury and death in different parts of the limbic systems (Montgomery et al, 1999). The mechanism involved in the pathogenesis appears to be linked to oxidative stress (Zaja-Milatovic et al, 2008). In various experimental studies, it has been demonstrated that antioxidants can prevent the excitotoxicity induced by agents such as glutamate and KA (Silva et al, 2008;Dong et al, 2009;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…KA-induced SE following systemic or intracerebroventricular injection of the drug initiates neuronal injury and death in different parts of the limbic systems (Montgomery et al, 1999). The mechanism involved in the pathogenesis appears to be linked to oxidative stress (Zaja-Milatovic et al, 2008). In various experimental studies, it has been demonstrated that antioxidants can prevent the excitotoxicity induced by agents such as glutamate and KA (Silva et al, 2008;Dong et al, 2009;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…12) In various experimental studies, it has been demonstrated that antioxidants can prevent the excitotoxicity induced by agents like glutamate and kainic acid. [13][14][15] Thus, antioxidants may have a potential role in preventing excitotoxicity induced seizure genesis.…”
mentioning
confidence: 99%
“…Studies were highly focused on the effect of antiinflammatory and antioxidant agents in brain upon injury by chemical adulteration, and viral or bacterial infections. Both types of agents showed to be effective in reducing F 4 -NeuroPs levels after injury, in particular in the cerebrum [42][43][44][45]. Levels of F 4 -NeuroPs in ischemicinduced rodent brain (cerebral cortex, hippocampus, gray matter) were also determined after α-lipoic acid treatment but no significant effect was found [46].…”
Section: Neuroprostanes and Neurofurans As Biomarkers In Metabolic Stmentioning
confidence: 99%
“…[ [43][44][45] ATM −/− and ATM +/+: forebrain and cerebellum Supplementation of EUK-189 is a low-molecular weight salen-manganese for 84 days.…”
Section: Lc-ms/ms [18]mentioning
confidence: 99%